REPRESENTASI IDEOLOGI DALAM NOVEL PASUNG JIWA KARYA OKKY MADASARI - Nurlaela Makmur; Jufri Jufri; Syamsudduha Syamsudduha (Universitas Negeri Makassar, 2022)
Representation of Ideology in the Novel Pasung Jiwa by Okky Madasari. This study aims to describe the form of expressive values in grammatical aspects in representing ideology. The type of research used in this research is qualitative research. The design used in this study is a qualitative descriptive design. The data in this study is the expressive value of the text in the novel Pasung Jiwa by Okky Madasari using Norman Fairclough's Critical Discourse Analysis approach. Meanwhile, the data source of this research comes from the novel Pasung Jiwa by Okky Madasari. Data collection techniques used inventory techniques, reading techniques, and note-taking techniques. Data analysis consists of three stages, namely: data reduction, data presentation, conclusions and leveraging research results. The results of the study show that the expressive form of grammatical aspects, verbal expressions support the form of diction against the ruling party, non-verbal forms of support strengthen the encouragement of minorities and support the supporters to be more empowered.